Melatih Kemampuan Bahasa Arab pada Siswa dalam Pembuatan atau Pembacaan Iklan di Madrasah Ibtidaiyah Tadzibun Nasyiin - Nuril Isabillah; Ainur Rofiq Sofa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the effectiveness of advertising-based learning strategies in training Arabic language skills of students at Tadzibun Nasyiin Elementary School. By utilizing the activity of making and reading advertisements both posters, brochures, and oral announcements students are encouraged to apply Arabic vocabulary and sentence structures contextually. Descriptive qualitative methods were used through classroom observations, interviews with teachers and students, and documentation of the results of advertising work. The results showed an increase in active participation and student confidence by an average of in the aspects of Arabic speaking and writing skills. The activity of making advertisements successfully facilitated the use of new vocabulary, while reading advertisements trained fluency and pronunciation. Thus, advertising-based strategies are recommended as an innovative alternative in Arabic language learning at the elementary school level.